A method for preparing a high-rigidity particle-reinforced aluminum-lithium based composite material
By using SiC particles coated with Al3Zr or Al3Sc in aluminum-lithium alloy, the problem of difficulty in interfacial reaction and dispersion between SiC particles and aluminum-lithium alloy in aluminum-lithium alloy is solved, and the preparation of aluminum-lithium-based composite materials with high stiffness and uniform structure is achieved. , significantly improves the strength and elastic modulus of the material.
Patent Information
- Application Number
- CN202310399843.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-04-14
AI Technical Summary
When carbon-containing ceramic particles such as SiC are used to enhance it in aluminum-lithium alloys, the interface reaction is severe and the particles are dispersed difficult, resulting in a reduced strengthening effect.
By mechanically alloying SiC or TiNC particles with Zr or Sc powder, Al3Zr or Al3Sc layer is formed, interface reaction is suppressed, and three-stage insulation and Ar gas rotary spray dispersion are carried out in the aluminum-lithium alloy melt to ensure the particles Uniform dispersion and high temperature stability.
It effectively inhibits the interface reaction between SiC particles and aluminum lithium alloy, improves the dispersion effect of particles, improves the strength and stiffness of aluminum lithium alloy, avoids the formation of brittle phases, and ensures the structural uniformity and strengthening effect of composite materials.
Smart Images

Figure CN116426786B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum-lithium alloys, and in particular to a method for preparing a high-rigidity particle-reinforced aluminum-lithium based composite material. Background Art
[0002] Aluminum alloy has the characteristics of low density and good thermal and electrical conductivity. It is one of the most widely used non-ferrous metal structural materials. In recent years, the leapfrog development of aerospace, underwater weapons and other equipment has put forward higher requirements for lightweight, high-strength and high-rigidity materials. Traditional commercial aluminum alloys have been difficult to meet the corresponding indicators. Compared with traditional aluminum alloys, aluminum-lithium alloys have low density and higher strength and rigidity. According to statistics, for every 1% mass fraction of lithium added to the aluminum alloy, the alloy density decreases by about 3% and the rigidity increases by about 6%. Therefore, lightweight and high-rigidity aluminum-lithium alloys have shown broad application prospects in important fields such as deep sea, deep earth, and deep space. The maximum lithium content of conventional cast aluminum-lithium alloys can reach about 3wt%, and its rigidity can reach up to about 81GPa, which is significantly higher than traditional aluminum alloys. However, there are the following problems with cast aluminum-lithium alloys at present:
[0003] Lithium is extremely active in chemical properties. Aluminum-lithium alloys with high lithium content are prone to oxidation, combustion, and gas absorption during high-temperature casting, which not only causes expensive lithium loss, but also seriously affects the purity of the aluminum-lithium alloy melt. Therefore, it is difficult to achieve a significant increase in the strength of aluminum-lithium alloys simply by increasing the lithium content;
[0004] The use of particle-reinforced aluminum-based composite materials is another effective method to improve the strength of aluminum-lithium alloys. At present, the preparation methods of particle-reinforced aluminum-based composite materials mainly include powder metallurgy, spray deposition, stirring casting, etc. However, the active aluminum-lithium alloy is prone to oxidation and combustion due to its large surface area during powder metallurgy and spray deposition.
[0005] To solve the above problems, the best solution is to use stirring casting. Since SiC particles have high rigidity, using SiC to reinforce aluminum-lithium alloy can effectively improve the strength and rigidity of the alloy. However, during the stirring casting process, how to suppress the harmful interface reaction between SiC particles and the matrix in the aluminum-lithium alloy composite material and better achieve the effective dispersion of SiC particles are key issues that need to be solved in the preparation of high-rigidity aluminum-lithium alloy composite materials. Based on this:
[0006] Reference patent application number CN202010328339.X-Ultra-light high elastic modulus carbon nanotube reinforced magnesium-lithium composite material and preparation method discloses: its components are: Li 9-16%, Zn 0.5-2%, Al 0.5-2%, Sc 0.02-0.2%, carbon nanotube C 0.1-2.5%, and the balance is Mg. During preparation, the carbon nanotubes are plated; the carbon nanotubes protected by the coating, magnesium chips and stearic acid are mixed and ball-milled and pressed into prefabricated blocks; under argon protection, the metal raw materials are melted to obtain alloy liquid, and the melt is stirred at a low speed; the temperature is lowered to near the liquidus temperature of the melt, and the prefabricated blocks are added during rapid mechanical stirring; after the stirring is completed, the temperature is heated to the casting temperature and cast. The present invention solves the problems of excessive reaction of Li and C and poor dispersion of carbon nanotubes in the matrix during the preparation process, so that the carbon nanotubes protected by the coating are stably and evenly dispersed in the matrix.
[0007] This prior art suppresses the interfacial reaction by lowering the reaction temperature between the reinforcing phase and the melt, but this method can only improve the magnesium-based composite material reinforced by carbon nanotubes, and cannot be used for reference in the preparation of other types of particle-reinforced metal-based composite materials, so it has low engineering adaptability. Although aluminum-lithium alloys reinforced with C-containing ceramic particles such as SiC have the characteristics of light weight, high rigidity, and high strength, SiC is very easy to react with the aluminum-lithium alloy melt to reduce the strengthening effect. In addition, the wettability of SiC particles with the aluminum-lithium alloy melt is poor, and it is difficult to achieve effective dispersion in the melt. Therefore, it is very important to invent a method that can both suppress the interfacial reaction between SiC particles and aluminum-lithium alloys and achieve their effective dispersion in the melt. Now a method for preparing a high-rigidity particle-reinforced aluminum-lithium-based composite material is proposed. Summary of the invention
[0008] The purpose of the present application is to provide a method for preparing a high-rigidity particle-reinforced aluminum-lithium based composite material, aiming to solve the problem of severe interface reaction and difficult particle dispersion when using SiC and other carbon-containing ceramic particles to reinforce aluminum-lithium alloy composite materials.
[0009] To achieve the above objectives, this application provides the following technical solutions:
[0010] The present application provides a method for preparing a high-rigidity particle-reinforced aluminum-lithium based composite material, the method comprising the following steps:
[0011] S1: mechanically alloying the reinforcement phase particles with Zr powder or Sc powder to obtain first reinforcement phase particles;
[0012] S2: screening the first reinforcement phase particles, and continuing to mechanically alloy with Al powder to obtain second reinforcement phase particles;
[0013] S3: Melting the aluminum-lithium alloy and heat-insulating the aluminum-lithium alloy melt in three stages, wherein the temperature of the first stage is 780-800°C, the temperature of the second stage is 670-690°C, and the temperature of the third stage is 720-740°C. In the second heat-insulating stage, the second reinforcing phase particles are added to the aluminum-lithium alloy melt.
[0014] Furthermore, the reinforcement phase particles are carbon-containing ceramic particles of SiC or TiNC, and the particle size of the ceramic particles is 300-500 meshes.
[0015] Furthermore, the step of mechanically alloying the reinforcement phase particles with Zr powder or Sc powder to obtain the first reinforcement phase particles comprises:
[0016] The ball-to-material ratio is 20:1-50:1, the ball milling time is 20-50 hours, and the particle size of the Zr powder or Sc powder is 500-700 meshes.
[0017] Furthermore, the step of screening the first reinforcement phase particles and continuing to mechanically alloy with Al powder to obtain the second reinforcement phase particles includes:
[0018] The ball-to-material ratio is 5:1-10:1, the ball milling time is 1-5 hours, and the particle size of the Al powder is 500-700 meshes.
[0019] Furthermore, the step of melting the aluminum-lithium alloy and heat-insulating the aluminum-lithium alloy melt in three stages, wherein the temperature of the first stage is 780-800° C., the temperature of the second stage is 670-690° C., and the temperature of the third stage is 720-740° C., and in the second heat-insulating stage, adding the second reinforcement phase particles to the aluminum-lithium alloy melt comprises:
[0020] During the first stage of heat preservation, 1% to 5% Zr or 1% to 5% Sc is first added;
[0021] The third insulation time is 1 to 5 minutes, and casting is performed quickly after insulation.
[0022] Furthermore, second reinforcement phase particles are added to the aluminum-lithium alloy melt and dispersed by Ar gas spinning spraying.
[0023] Furthermore, in the step S3, the second reinforcement phase particles are added to the aluminum-lithium alloy melt in the second heat preservation stage, and a dense SiO2 layer is formed on the surface of SiC or TiNC by high temperature oxidation. The generation of Al4C3 is avoided by the reaction of SiO2 with aluminum. The specific reaction is as follows:
[0024] Furthermore, the preparation process of the molten aluminum-lithium alloy is:
[0025] S1: Place 3 kg of aluminum-lithium alloy in the crucible and preheat the crucible and tools to 200 °C in advance;
[0026] S2: Heat to 750°C to melt the aluminum-lithium alloy. After it is completely melted, skim off the slag, stir the alloy liquid, and adjust the temperature to 710°C and keep it warm for 5 minutes;
[0027] S3: Using a bell jar, 0.4wt.%, 12g of hexachloroethane wrapped in aluminum foil was pressed into the aluminum liquid and refined for 10min;
[0028] S4: After refining, the aluminum-lithium alloy is transferred into a stirring composite furnace, and a covering agent is added to the surface of the alloy liquid. The covering agent is potassium chloride, sodium chloride, and cryolite.
[0029] The present application provides a method for preparing a high-rigidity particle-reinforced aluminum-lithium based composite material, which has the following beneficial effects:
[0030] (1) The present invention can form an Al3Zr or Al3Sc layer on the SiC surface. Since Al3Zr or Al3Sc has high thermal stability, the presence of this intermediate layer can effectively inhibit the interface reaction between SiC particles and aluminum-lithium alloys, avoid the generation of brittle Li2C2 and Al4C3, and effectively ensure the strength and rigidity of the aluminum-lithium based composite material;
[0031] (2) The present invention uses Al3Zr or Al3Sc to coat the SiC reinforcement phase. Since Al3Zr and Al3Sc both have good wettability with aluminum melt, the present invention can improve the problem of poor dispersion effect caused by poor wettability of SiC with aluminum melt.
[0032] (3) The Al3Zr or Al3Sc-wrapped SiC reinforced aluminum-lithium alloy composite material prepared by the present invention also has the characteristic of fine grain size, which can avoid the problem of enrichment caused by the reinforcement phase being pushed to the grain boundary by the growing dendrites. Therefore, the structure of the aluminum-lithium alloy composite material prepared by the present invention will be more uniform;
[0033] (4) The three-stage heat preservation process designed in the present invention can not only ensure the fluidity of the aluminum-lithium alloy melt and reduce the defects in the composite material ingot, but also avoid the dissolution of the reinforcement phase particles in the high-temperature melt, thereby maximizing the strengthening effect of the reinforcement phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of a process for preparing a high-rigidity particle-reinforced aluminum-lithium based composite material according to an embodiment of the present application;
[0035] Figure 2 A schematic diagram of the organization of reinforcement phase particles in a melt preparation process according to an embodiment of the present application;
[0036] Among them, 1 is SiC particles, 2 is a Zr or Sc layer, 3 is an Al3Zr or Al3Sc layer, and 4 is an aluminum-lithium alloy melt.
[0037] The implementation, functional features and advantages of the present application will be further described in conjunction with embodiments and with reference to the accompanying drawings. Implementation
[0038] It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0039] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0040] Reference Figure 1 , which is a schematic diagram of a process for preparing a high-rigidity particle-reinforced aluminum-lithium based composite material proposed in this application;
[0041] S1: Mechanically alloying the reinforcement phase particles with Zr powder or Sc powder to obtain first reinforcement phase particles, wherein the reinforcement phase particles are carbon-containing ceramic particles of SiC or TiNC, the particle size of the ceramic particles is 300-500 mesh, the ball-to-material ratio is 20:1-50:1, the ball milling time is 20-50h, and the particle size of the Zr powder or Sc powder is 500-700 mesh;
[0042] In this step, Zr or Sc is used as the metal powder for the first step of mechanical alloying. This is mainly because the crystal structures of Zr and SiC are both hexagonal structures. In this way, since the crystal structure of the reinforcement phase particles is consistent with that of the mechanically alloyed metal powder, it is easier to form Zr enrichment on the surface of SiC, which is beneficial to improving the interface bonding force between the SiC particles and the Zr layer; the reinforcement phase particles are carbon-containing ceramic particles such as SiC and TiNC, and the particle size of the ceramic particles is 300~500 mesh. The modulus of carbon-containing ceramic particles such as SiC and TiNC is high, and the reinforcement effect in aluminum-lithium alloy is better and more obvious.
[0043] In step S1, the ball-to-material ratio is 20:1~50:1, the ball milling time is 20~50h, the particle size of Zr powder and Sc powder is smaller than that of the reinforcing phase particles, and the particle size is 500~700 mesh; in the present application, the ball-to-material ratio is larger than that of the traditional ball milling process, and the ball milling time is also higher, which is mainly due to the fact that SiC, Zr, Sc, etc. are all hard particles, and the required temperature and pressure for mechanical alloying are higher, so it is easy to form a metallurgical layer only under the condition of a higher ball-to-material ratio. In addition, a higher ball-to-material ratio and a longer ball milling time are conducive to improving the interface bonding force between SiC and Zr or Sc, avoiding interface cracking during subsequent mechanical alloying and casting processes, which causes SiC to be directly exposed to the aluminum-lithium alloy melt, wherein the smaller particle size of Zr powder and Sc powder is conducive to increasing the contact area between them and SiC particles, and obtaining a better mechanical alloying effect.
[0044] S2: Screening the first reinforcement phase particles, and continuing to mechanically alloy with Al powder to obtain second reinforcement phase particles, the ball-to-material ratio is 5:1-10:1, the ball milling time is 1-5 hours, and the particle size of the Al powder is 500-700 mesh;
[0045] In this step, the first reinforcement phase particles are mechanically alloyed with Al powder. In order to form an Al3Zr or Al3Sc transition layer on the surface of the reinforcement phase particles, Al3Zr and Al3Sc have a good wetting effect on the aluminum-lithium alloy melt, so the SiC reinforcement phase particles with the Al3Zr or Al3Sc transition layer are more easily dispersed in the aluminum-lithium alloy melt; and Al3Zr is a stable intermetallic compound, which can remain stable within the melting temperature range of the aluminum alloy and does not react with other alloying elements, thereby avoiding the reaction of SiC particles with aluminum and lithium elements and inhibiting the occurrence of harmful interface reactions; in addition, since Al3Zr and Al3Sc have a good lattice match with α-Al, the SiC particles coated with Al3Zr or Al3Sc can be added as heterogeneous nucleation cores of α-Al. During the solidification process of the aluminum-lithium alloy, these reinforcement phase particles are not easily pushed to the grain boundary by the growing dendrites and aggregated, but directly exist in the α-Al dendrites, not only the α-Al grains can be refined, but the distribution of the reinforcement phase particles will also be more uniform.
[0046] The ball-to-material ratio is 5:1-10:1, the ball milling time is 1-5h, and the particle size of the Al powder is 500-700 mesh, so that the Zr or Sc attached to the surface of SiC reacts with Al to generate Al3Zr or Al3Sc. In this step, the ball-to-material ratio and the ball milling time are lower than those in step S1, in order to avoid the Zr layer or Sc layer from peeling off and separating from SiC during the ball milling process in this step.
[0047] S3: Melting the aluminum-lithium alloy and heat-insulating the aluminum-lithium alloy melt in three stages, wherein the temperature of the first stage is 780-800°C, the temperature of the second stage is 670-690°C, and the temperature of the third stage is 720-740°C, and the second reinforcing phase particles are added to the aluminum-lithium alloy melt in the second heat-insulating stage; during the heat-insulating process of the first stage, 1%-5% of Zr or 1%-5% of Sc is first added, the heat-insulating time of the third stage is 1-5 minutes, and casting is performed quickly after heat-insulating, and the second reinforcing phase particles are added to the aluminum-lithium alloy melt, and Ar gas rotating blowing dispersion is adopted.
[0048] In this step, 1% to 5% Zr or 1% to 5% Sc by mass is first added during the first heat preservation process in order to promote the full dissolution of Zr or Sc in the high temperature range of 780 to 800°C, so that the Zr content or Sc content in the aluminum-lithium alloy melt reaches a supersaturated state in advance; when SiC coated with Al3Zr or Al3Sc is added during the second heat preservation process, from a thermodynamic point of view, the Al3Zr or Al3Sc on the surface of SiC will be more stable and less likely to dissolve in the aluminum-lithium alloy melt. It is easy to be dissolved. The second holding temperature is only 670~690℃. At this time, due to the low melt temperature, the viscosity of the aluminum-lithium alloy melt at a lower holding temperature will increase, which is beneficial to improve the dispersion of the reinforcement phase in the melt; the third holding time is 1~5min and casting is carried out quickly after holding, in order to reduce the existence time of SiC particles coated with Al3Zr or Al3Sc at high temperature as much as possible. At the same time, the higher casting temperature effectively ensures the good fluidity of the melt and avoids the formation of cold shut and insufficient casting defects in the ingot.
[0049] When adding the second reinforcement phase particles to the aluminum-lithium alloy melt, the Ar gas rotary spray dispersion method is adopted, so that the reinforcement phase particles are added to the melt under the auxiliary conditions of the Ar gas carrier flow. Under the conditions of argon spraying, the dispersion effect of the SiC particles coated with Al3Zr or Al3Sc will be better, and during the stirring process, since the Ar gas continuously escapes from the melt, an effective protective gas atmosphere can be formed above the melt to isolate the air. This avoids the problem that the melt is easy to inhale air due to conventional stirring, which leads to severe oxidation of the highly active aluminum-lithium alloy melt. Example
[0050] First, mechanical alloying of SiC reinforcement phase particles and Zr powder was performed. SiC particles with a particle size of 300 mesh and Zr powder with a particle size of 500 mesh were selected for mechanical alloying, wherein the ball-to-material ratio was 20:1 and the ball milling time was 20 hours. Subsequently, the reinforcement phase particles were sieved with a stainless steel mesh and then mechanically alloyed with Al powder with a particle size of 500 mesh, the ball-to-material ratio was 5:1, and the ball milling time was 1 hour.
[0051] Secondly, the aluminum-lithium alloy composite material was melt-casted. First, the Al-3Li alloy was melted and 1% Zr was added at 780°C. Then the melt temperature was lowered to 670°C, and 5% SiC particles after mechanical alloying were added to the melt by Ar gas spinning spray dispersion. Finally, the melt temperature was raised to 720°C and kept warm for 1 minute before casting. After microstructural observation, no Li2C2 and Al4C3 appeared at the interface between SiC particles and the aluminum-lithium alloy matrix, and the reinforcement phase particles were well dispersed in the aluminum-lithium alloy matrix. According to the ultrasonic resonance spectrum method, the elastic modulus of the prepared aluminum-lithium alloy was as high as 91GPa, which was 16GPa higher than the elastic modulus of the Al-3Li alloy without adding reinforcement phase particles (75GPa). Example
[0052] First, mechanical alloying of SiC reinforcement phase particles and Zr powder was performed. SiC particles with a particle size of 400 mesh and Zr powder with a particle size of 600 mesh were selected for mechanical alloying, wherein the ball-to-material ratio was 30:1 and the ball milling time was 30 hours. Subsequently, the reinforcement phase particles were sieved with a stainless steel mesh and then mechanically alloyed with Al powder with a particle size of 600 mesh, with a ball-to-material ratio of 8:1 and a ball milling time of 3 hours.
[0053] Secondly, the aluminum-lithium alloy composite material was melt-casted. First, the Al-3Li alloy was melted and 3% Zr was added at 790℃. Then the melt temperature was lowered to 680℃, and 5% SiC particles after mechanical alloying were added to the melt by Ar gas spinning spray dispersion. Finally, the melt temperature was raised to 730℃ and kept warm for 3 minutes before casting. According to microstructural observation, no Li2C2 and Al4C3 appeared at the interface between SiC particles and aluminum-lithium alloy matrix, and the reinforcement phase particles were well dispersed in the aluminum-lithium alloy matrix. According to the ultrasonic resonance spectrum method, the elastic modulus of the prepared aluminum-lithium alloy was as high as 88GPa, which was 13GPa higher than the elastic modulus (75GPa) of the Al-3Li alloy without reinforcement phase particles. Example
[0054] First, mechanical alloying of SiC reinforcement phase particles and Zr powder was performed. SiC particles with a particle size of 500 mesh and Zr powder with a particle size of 700 mesh were selected for mechanical alloying, wherein the ball-to-material ratio was 50:1 and the ball milling time was 50 hours. Subsequently, the reinforcement phase particles were sieved with a stainless steel mesh and then mechanically alloyed with Al powder with a particle size of 700 mesh, with a ball-to-material ratio of 10:1 and a ball milling time of 5 hours.
[0055] Secondly, the aluminum-lithium alloy composite material was melt-casted. First, the Al-3Li alloy was melted and 1% Zr was added at 800℃. Then the melt temperature was lowered to 690℃, and 5% SiC particles after mechanical alloying were added to the melt by Ar gas spinning spray dispersion. Finally, the melt temperature was raised to 740℃ and kept warm for 5 minutes before casting. After microstructural observation, no Li2C2 and Al4C3 appeared at the interface between SiC particles and the aluminum-lithium alloy matrix, and the reinforcement phase particles were well dispersed in the aluminum-lithium alloy matrix. According to the ultrasonic resonance spectrum method, the elastic modulus of the prepared aluminum-lithium alloy was as high as 93GPa, which was 18GPa higher than the elastic modulus (75GPa) of the Al-3Li alloy without adding reinforcement phase particles. Example
[0056] First, mechanical alloying of TiNC reinforcement phase particles and Sc powder was performed. TiNC particles with a particle size of 300 mesh and Sc powder with a particle size of 500 mesh were selected for mechanical alloying, wherein the ball-to-material ratio was 20:1 and the ball milling time was 20 hours. Subsequently, the reinforcement phase particles were sieved with a stainless steel mesh and then mechanically alloyed with Al powder with a particle size of 500 mesh, with a ball-to-material ratio of 5:1 and a ball milling time of 1 hour.
[0057] Secondly, the aluminum-lithium alloy composite material was melt-casted. First, the Al-3Li alloy was melted and 1% Sc was added at 780°C. Then, the melt temperature was lowered to 670°C, and 5% TiNC particles after mechanical alloying were added to the melt by Ar gas spinning spray dispersion. Finally, the melt temperature was raised to 720°C and kept warm for 1 minute before casting. According to microstructural observation, no Li2C2 and Al4C3 appeared at the interface between TiNC particles and the aluminum-lithium alloy matrix, and the reinforcement phase particles were well dispersed in the aluminum-lithium alloy matrix. According to the ultrasonic resonance spectrum method, the elastic modulus of the prepared aluminum-lithium alloy was as high as 90GPa, which was 15GPa higher than the elastic modulus (75GPa) of the Al-3Li alloy without adding reinforcement phase particles. Example
[0058] First, mechanical alloying of TiNC reinforcement phase particles and Sc powder was carried out.
[0059] TiNC particles with a particle size of 400 mesh and Sc powder with a particle size of 600 mesh were selected for mechanical alloying, wherein the ball-to-material ratio was 30:1 and the ball milling time was 30 hours. Subsequently, the reinforcement phase particles were sieved with a stainless steel mesh and then mechanically alloyed with Al powder with a particle size of 600 mesh, with a ball-to-material ratio of 8:1 and a ball milling time of 3 hours.
[0060] Secondly, the aluminum-lithium alloy composite material was melt-casted. First, the Al-3Li alloy was melted and 3% Sc was added at 790°C. Then the melt temperature was lowered to 680°C, and 5% TiNC particles after mechanical alloying were added to the melt by Ar gas spinning spray dispersion. Finally, the melt temperature was raised to 730°C and kept warm for 3 minutes before casting. According to microstructural observation, no Li2C2 and Al4C3 appeared at the interface between TiNC particles and the aluminum-lithium alloy matrix, and the reinforcement phase particles were well dispersed in the aluminum-lithium alloy matrix. According to the ultrasonic resonance spectrum method, the elastic modulus of the prepared aluminum-lithium alloy was as high as 88GPa, which was 13GPa higher than the elastic modulus (75GPa) of the Al-3Li alloy without adding reinforcement phase particles. Example
[0061] First, mechanical alloying of TiNC reinforcement phase particles and Sc powder was performed. TiNC particles with a particle size of 500 mesh and Sc powder with a particle size of 700 mesh were selected for mechanical alloying, wherein the ball-to-material ratio was 50:1 and the ball milling time was 50 hours. Subsequently, the reinforcement phase particles were sieved with a stainless steel mesh and then mechanically alloyed with Al powder with a particle size of 700 mesh, with a ball-to-material ratio of 10:1 and a ball milling time of 5 hours.
[0062] Secondly, the aluminum-lithium alloy composite material was melt-casted. First, the Al-3Li alloy was melted and 1% Sc was added at 800℃. Then the melt temperature was lowered to 690℃, and 5% TiNC particles after mechanical alloying were added to the melt by Ar gas spinning spray dispersion. Finally, the melt temperature was raised to 740℃ and kept warm for 5 minutes before casting. According to microstructural observation, no Li2C2 and Al4C3 appeared at the interface between TiNC particles and the aluminum-lithium alloy matrix, and the reinforcement phase particles were well dispersed in the aluminum-lithium alloy matrix. According to the ultrasonic resonance spectrum method, the elastic modulus of the prepared aluminum-lithium alloy was as high as 93GPa, which was 18GPa higher than the elastic modulus (75GPa) of the Al-3Li alloy without adding reinforcement phase particles.
[0063] Comparative Example 1
[0064] The preparation method of this comparative example is basically the same as that of Example 1, except that the mechanical alloying of SiC particles and Zr powder is not performed, but the mechanical alloying of SiC particles and Al powder is performed directly. The results show that a large number of brittle phases such as Li2C2 and Al4C3 appear at the interface between SiC particles and the aluminum-lithium alloy matrix. The elastic modulus of the prepared aluminum-lithium alloy measured by ultrasonic resonance spectrum method is only 64GPa. This is mainly because the mechanical alloying of SiC particles and Zr powder is not performed, and there is no Al3Zr layer to protect SiC at the interface between SiC and the matrix, so harmful interface reactions occur, resulting in a decrease in the elastic modulus of the composite material.
[0065] Comparative Example 2
[0066] The preparation method of this comparative example is basically the same as that of Example 1, except that after the mechanical alloying of SiC and Zr powders is completed, the mechanical alloying of the reinforcing phase particles and Al powder is not performed. The results show that some brittle phases such as Li2C2 and Al4C3 appear at the interface between SiC particles and the aluminum-lithium alloy matrix. The elastic modulus of the prepared aluminum-lithium alloy measured by ultrasonic resonance spectrum method is only 71GPa. This is mainly because the Zr layer is directly exposed to the high-temperature aluminum-lithium alloy melt when it is directly added to the aluminum-lithium alloy melt without mechanical alloying with Al powder. The Al element and Li element will quickly diffuse through the Zr layer and react with the SiC matrix to form brittle phases such as Li2C2 and Al4C3.
[0067] Comparative Example 3
[0068] The preparation method of this comparative example is basically the same as that of Example 1, except that the aluminum-lithium alloy melt is not subjected to three-stage heat preservation, and the melt temperature is always controlled at 720°C. The results show that a small amount of brittle phases such as Li2C2 and Al4C3 appear at the interface between SiC particles and the aluminum-lithium alloy matrix. The elastic modulus of the prepared aluminum-lithium alloy measured by ultrasonic resonance spectrum method is only 61GPa. This is mainly because when Zr alloying is carried out at a high temperature of 720°C, Zr cannot be fully dissolved in the melt, so the Zr content in the melt is low. After Al3Zr is subsequently added, it is easy to dissolve in a small amount in the aluminum-lithium alloy melt, so a harmful interface reaction occurs, resulting in a decrease in the elastic modulus of the composite material.
[0069] Comparative Example 4
[0070] The preparation method of this comparative example is basically the same as that of Example 1, except that the ratio of ball to material is 10:1 when the reinforcing phase and Zr powder are mechanically alloyed. The results show that a small amount of brittle phases such as Li2C2 and Al4C3 appear at the interface between SiC particles and the aluminum-lithium alloy matrix. The elastic modulus of the prepared aluminum-lithium alloy measured by ultrasonic resonance spectrum method is 77GPa. This is mainly due to the fact that the ratio of ball to material is too small, resulting in a small pressure between SiC and Zr during ball milling, and the Zr layer on the surface of SiC is too thin, so the subsequent Al3Zr layer is also thin. Harmful interface reactions occurred during the smelting process, resulting in a decrease in the elastic modulus of the composite material.
[0071] Comparative Example 5
[0072] The preparation method of this comparative example is basically the same as that of Example 1, except that Zr is not added in the first heat preservation process during smelting. The results show that a large number of brittle phases such as Li2C2 and Al4C3 appear at the interface between SiC particles and the aluminum-lithium alloy matrix. The elastic modulus of the prepared aluminum-lithium alloy is 71GPa measured by ultrasonic resonance spectrum method. This is mainly because the Zr content in the melt has not reached supersaturation, so a small amount of Al3Zr on the surface of SiC is dissolved during the smelting process, resulting in harmful interface reactions and a decrease in the elastic modulus of the composite material.
[0073] Comparative Example 6
[0074] The preparation method of this comparative example is basically the same as that of Example 1, except that: Ar gas rotary blowing is not used when dispersing the reinforcing phase particles, but mechanical stirring is used for dispersion. The results show that there are a large number of defects such as pores and oxidation inclusions in the prepared composite material. The elastic modulus of the prepared aluminum-lithium alloy is 65GPa measured by ultrasonic resonance spectrum method. This is mainly because there is no Ar gas protection during the mechanical stirring process, so a large amount of air is involved, the melt oxidation inhalation is serious, and the elastic modulus of the composite material is reduced.
[0075] Comparative Example 7
[0076] The preparation method of this comparative example is basically the same as that of Example 1, except that: during the casting process, the third stage of the insulation temperature is kept for 10 minutes before casting. The results show that trace brittle phases such as Li2C2 and Al4C3 appear at the interface between the SiC particles and the aluminum-lithium alloy matrix. The elastic modulus of the prepared aluminum-lithium alloy is 82GPa measured by ultrasonic resonance spectrum method. This is mainly due to the high insulation temperature of the third stage, and the Al3Zr coated on the outer layer of the SiC particles is in contact with the aluminum-lithium alloy melt for a long time at high temperature, resulting in harmful interface reactions, so the elastic modulus of the composite material is reduced.
[0077] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, device, article or method including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, device, article or method. In the absence of further restrictions, an element defined by the sentence "includes a ..." does not exclude the presence of other identical elements in the process, device, article or method including the element.
[0078] The above description is only a preferred embodiment of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
[0079] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-rigidity particle-reinforced aluminum-lithium based composite material, characterized in that: include: S1: mechanically alloying the reinforcement phase particles with Zr powder or Sc powder to obtain first reinforcement phase particles, wherein the reinforcement phase particles are carbon-containing ceramic particles of SiC or TiNC; S2: screening the first reinforcement phase particles, and continuing to mechanically alloy with Al powder to obtain second reinforcement phase particles; S3: Melting the aluminum-lithium alloy and heat-insulating the aluminum-lithium alloy melt in three stages, wherein the temperature of the first stage is 780-800°C, the temperature of the second stage is 670-690°C, and the temperature of the third stage is 720-740°C. In the second heat-insulating stage, the second reinforcing phase particles are added to the aluminum-lithium alloy melt.
2. The method for preparing the high-rigidity particle-reinforced aluminum-lithium based composite material according to claim 1, characterized in that: The reinforcement phase particles are carbon-containing ceramic particles of SiC or TiNC, and the particle size of the ceramic particles is 300-500 meshes.
3. The method for preparing the high-rigidity particle-reinforced aluminum-lithium based composite material according to claim 1, characterized in that: The step of mechanically alloying the reinforcement phase particles with Zr powder or Sc powder to obtain the first reinforcement phase particles comprises: The ball-to-material ratio is 20:1-50:1, the ball milling time is 20-50 hours, and the particle size of the Zr powder or Sc powder is 500-700 meshes.
4. The method for preparing the high-rigidity particle-reinforced aluminum-lithium based composite material according to claim 1, characterized in that: The step of screening the first reinforcement phase particles and continuing to mechanically alloy with Al powder to obtain the second reinforcement phase particles comprises: The ball-to-material ratio is 5:1-10:1, the ball milling time is 1-5 hours, and the particle size of the Al powder is 500-700 meshes.
5. The method for preparing a high-rigidity particle-reinforced aluminum-lithium based composite material according to claim 1, characterized in that: The step of melting the aluminum-lithium alloy and heat-insulating the aluminum-lithium alloy melt in three stages, wherein the temperature of the first stage is 780-800° C., the temperature of the second stage is 670-690° C., and the temperature of the third stage is 720-740° C., and in the second heat-insulating stage, adding the second reinforcement phase particles to the aluminum-lithium alloy melt comprises: During the first stage of heat preservation, 1% to 5% Zr or 1% to 5% Sc is first added; The third insulation time is 1 to 5 minutes, and casting is performed quickly after insulation.
6. The method for preparing the high-rigidity particle-reinforced aluminum-lithium based composite material according to claim 5, characterized in that: The second reinforcement phase particles are added into the aluminum-lithium alloy melt and dispersed by Ar gas swirling spraying.
7. The method for preparing a high-rigidity particle-reinforced aluminum-lithium based composite material according to claim 1, characterized in that: In the step S3, the second reinforcing phase particles are added to the aluminum-lithium alloy melt in the second insulation stage, and a dense SiO2 layer is formed on the surface of SiC or TiNC by high-temperature oxidation. The generation of Al4C3 is avoided by the reaction of SiO2 with aluminum. The specific reaction is as follows: 3SiC+4Al→Al4C3+3Si, 2SiC+2Li→Li2C2+2Si.
8. The method for preparing a high-rigidity particle-reinforced aluminum-lithium based composite material according to claim 1, characterized in that: The preparation process of the molten aluminum-lithium alloy is: S1: Place 3 kg of aluminum-lithium alloy in the crucible and preheat the crucible and tools to 200 °C in advance; S2: Heat to 750°C to melt the aluminum-lithium alloy. After it is completely melted, skim off the slag, stir the alloy liquid, and adjust the temperature to 710°C and keep it warm for 5 minutes; S3: Using a bell jar, 0.4wt.%, 12g of hexachloroethane wrapped in aluminum foil was pressed into the aluminum liquid and refined for 10min; S4: After refining, the aluminum-lithium alloy is transferred into a stirring composite furnace, and a covering agent is added to the surface of the alloy liquid. The covering agent is potassium chloride, sodium chloride, and cryolite.
